ANALISIS SOSIAL HASSAN HANAFI DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Muhammad Lutfi (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2023)
Abstrac This paper illustrates Hassan Hanafi's thoughts about his rejection of westernization. Western superior justification is just a Western guise in smoothing the occupation of the East. Hassan Hanafi tried to counter with his idea of ​​Occidentalism. An idea that was born from the project of Islamic Left thinking and al-Turats wa al-Tajdid. This paper is a literature review that was extracted from several primary and secondary sources. The purpose of this paper is to examine the thoughts of Hassan Hanafi, who then draws on implication for current thinking. Abstrak Tulisan ini menggambarkan pemikiran Hassan Hanafi tentang penolakannya terhadap westernisasi. Justifikasi superior Barat hanyalah sebuah kedok Barat dalam memuluskan penjajahan terhadap Dunia Timur. Hassan Hanafi mencoba mengkunter dengan gagasannya berupa Oksidentalisme. Sebuah gagasan yang lahir dari proyek pemikiran Kiri Islam dan al-Turats wa al-Tajdid. Tulisan ini merupakan kajian pustaka yang digali dari beberapa sumber primer dan sekunder. Tujuan tulisan ini ialah untuk mengkaji pemikiran Hassan Hanafi yang kemudian ditarik pada sebuah implikasi terhadap pemikiran di masa sekarang.